MANAGEMENT OF CT SCAN HEAD EXAMINATION IN NON-COOPERATIVE INFANTS WITH CLINICAL INTRACEREBRAL HEMMORAGE AND SUBARACHNOID HEMMORAGE IN THE RADIOLOGY INSTALLATION OF AWAL BROS PANAM HOSPITAL - Amreski Amreski; Ernita Safitri (Medical Imaging and Radiation Protection Research Journal, 2024)
Background: Head injuries in infants require rapid and accurate imaging examinations to detect intracranial abnormalities, including intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH). Head CT scanning is one of the primary imaging modalities because it can provide rapid visualization of intracranial structures. However, examinations in non-cooperative infants present challenges due to patient movement, which can produce artifacts and reduce image quality. This study aimed to determine the management of head CT examinations in a non-cooperative infant with clinical ICH and SAH and to assess the ability of the examination technique to support diagnosis. Methods: This study employed a qualitative descriptive method with a case study approach. Data were obtained through observation, documentation, and interviews with the radiographer, referring physician, and the patient's family. Results: The examination was performed with the patient in the supine position, head first, with the indicator light aligned with the mid-sagittal plane (MSP) and mid-coronal plane (MCP), and the positioning reference point at the glabella. The examination parameters included a slice thickness of 5 mm, FOV of 25.0, 120 kV, 50 mA, pitch of 0.875:1, window width of 150, and window level of 40. In the non-cooperative patient, a helical technique was used to shorten the examination time and minimize motion artifacts. Conclusion: The management of head CT examination in a non-cooperative infant with clinical ICH and SAH can produce adequate diagnostic images and support the establishment of a diagnosis. The helical technique provides an effective solution for overcoming limitations in patient cooperation during the examination.